Levels of immunoreactive dynorphin A1-13 during development of morphine dependence in rats - Wan Xin-Wang; Li Wan-Hai; Huang Mao; You Zhen-Dong; Tan Ye-Xiong; Lu Chang-Lin; Gong Ze-Hui (Acta Pharmacologica Sinica, 2016)
AIM: To study the relationship between the levels of immunoreactive dynorphin A1-13 (ir-dynorphin A1-13) and the degree of morphine dependence. METHODS: The levels of ir-dynorphin A1-13 in discrete brain regions, spinal cord, and plasma in rats were determined by radioimmunoassay, and the degree of morphine dependence was assessed by scoring withdrawal signs on d 3, d 6, and d 12. RESULTS: Morphine injection s.c. decreased the levels of ir-dynorphin A1-13 in spinal cord, pituitary, and plasma. The levels of ir-dynorphin A1-13 in hippocampus and hypothalamus were increased. No changes in cortex, midbrain, cerebellum, pons, and medulla were observed. With continuous injection of morphine, withdrawal signs scores were increased on d 6, but there was no difference between the scores of d 6 and d 12. CONCLUSION: The changes of the levels of endogenous ir-dynorphin A1-13 in pituitary, spinal cord, and plasma were compatible with the degree of morphine dependence.